Ejercicios de métodos matemáticos - Levi Lattes, Enzo; Echavez Aldape, Gabriel; Arreguín Cortés, Felipe I.; Pereyra Díaz, Domitilo (Facultad de Ingeniería, 1995)
Ejercicios de métodos matemáticos
Ejercicios de métodos matemáticos
Keywords: Ejercicios; Métodos matemáticos